TEKNOLOGI PENETASAN TELUR BURUNG MALEO (Macrocephalon maleo Sal. Muller 1846) SEBAGAI UPAYA KONSERVASI - Mobius Tanari; Yohan Rusiyantono; Hafsah Hafsah (Universitas Tadulako, 2008)
The objective of the research was to determine the best hatching technique of maleo eggs from various measures such as as ex-situ, incubation time and hatch capacity of maleo bird using incubator. Thirty eggs were collected from the Lore Lindu National Park of Palu, Province of central Sulawesi according to an accidental sampling. The results showed that the mean weight of eggs from the National Lore Lindu Park was 208.80 ± 12.30 g, egg length was 102.85 ± 0.034 mm while egg width was 60.66 ± 0.02 mm. The mean of incubator temperature of was 34.061 ± 0.19ºC with relative humidity of 70.87 ± 1.43 %. The percent of hatching eggs for incubation time of 53-55 days was 23.81 %, for that of 56-58 days was 23.81 %, for that of 59-61 days was 42.85 % and for that of 62-64 days was 9.53 %. Thus, the average time for the eggs to hatch was 58.47 ± 2.88 days at the hatched rate of 70%. Based on such figures above, it can be concluded that the hatching technique using incubator could become the conservation strategy for maleo bird in Sulawesi particularly in Central Sulawesi Province